A Submucosal Lipoma of Small Intestine as an Unpredictable Cause of Intussusception and Intestinal Obstruction; A Case Report and Literature Review - Mohammed, Maisa Hashem (Asian Pacific Journal of Cancer Biology, 2022)
Background: Intussusception refers to telescoping of one intestinal segment and its mesentery into an adjacent intestinal loop. It is a rather frequent entity in infants with an excellent prognosis. However, intussusception in adults is a rare surgical problem which almost always results from a pathological cause which interferes with intestinal motility. Methods: A 71-year-old woman suffered from severe colicky abdominal pain, nusea and vomiting. Clinical examination and radiological findings highly suspected a case of intussusception. Exploratory laparotomy and relief of intussusception were achieved. There was a soft intraluminal small intestinal mass. Resection anastomosis of the small intestinal loop which harbored the polyp was done. The specimen was subjected to pathological evaluation. Results: The pathological evaluation revealed a submucosal lipoma of the small intestine, protruded in the intestinal lumen as a pedunculated polyp with intact overlying mucosa. Conclusion: Lipoma of the small intestine should be suspected in any case of intussusception, especially in adults.